Southern Andean Stigmella sinuosa complex (Lepidoptera, Nepticulidae): unraveling problematic taxonomy with a pictorial key of adults? - Stonis, Jonas R.; Remeikis, Andrius (Zootaxa, 2016)
On the basis of morphological studies of a collection sample from the southern Andes of Argentina and Chile, we describe and name two new species of Stigmella Schrank (Lepidoptera: Nepticulidae): S. sinuosa Remeikis & Stonis, sp. nov. and S. mevia Remeikis & Stonis, sp. nov. Other two new species are documented but left unnamed. All treated taxa belong to a newly designated S. sinuosa complex that belongs to the S. salicis group. The S. sinuosa complex contains cryptic species. We also discuss the differentiation of the species of the complex by using morphological characters.